Impact of Ready-to-Drink Beverages on the Color Stability of Acrylic Resin Teeth in Removable Partial Dentures: An In Vitro Study - Wirahadikusumah, Andy; Anggarawati, Nanik (Dentistry Faculty, 2024)
Background: Due to its many advantages, acrylic resin is the most widely used material for denture teeth in removable partial dentures. However, acrylic resin teeth are known to absorb colorants. As a substitute for natural teeth, these resin teeth are frequently exposed to foods and beverages consumed by patients. Popular ready-to-drink (RTD) beverages in Indonesia include coffee, orange juice, and carbonated drinks, each containing dyes that may affect the color stability of acrylic resin teeth. Objective: This study aims to assess the effect of various RTD beverages on the color stability of different acrylic resin denture teeth commonly used in Indonesia. Materials and Methods: The study sample consisted of 40 acrylic resin denture teeth samples, specifically maxillary central incisors, from the Ortolux Top and New Ace brands. The samples were immersed in distilled water, coffee (Nescafe), orange juice (Minute Maid Pulpy Orange), and carbonated soda (Coca-Cola) for five days in an incubator at 37C. Color measurements were taken using a VITA Easyshade V spectrophotometer before and after immersion. Statistical analysis was performed using a one-way ANOVA test. Results: Coffee and Carbonated soda caused color changes in both brands of acrylic resin teeth, affecting the E, L, C, and H values, making the samples darker, more yellowish, and decreasing color saturation. However, orange juice only affected the L and C values of the New Ace brand, causing the samples to appear darker and less saturated. Conclusion: Some RTD beverages (coffee, orange juice, and carbonated drinks) can lead to discoloration of acrylic resin teeth, making them darker and less saturated.